Resistance in urdbean against yellow mosaic, leaf crinkle and Cercospora leaf spot diseases in natural epiphytotic condition at Keonjhar district of Odisha - T.R. MOHANTY, POLY SAHA*, JAYWANT K. SINGH and (Indian Phytopathology, 2017)
The present investigation aimed to identify resistance in urdbean (Vigna mungo) against yellow mosaic disease (YMD), urdbean leaf crinkle disease complex (ULCD) and Cercospora leaf spot (CLS) in a field trial conducted at Regional Research and Technology Transfer Station, Keonjhar (AICRP on MULLaRP sub-centre), OUAT, Odisha. Twenty four urdbean genotypes were screened in the summer season of the year of 2012- 2013 and 2013-2014. The severity of YMD and CLS was recorded following 0-9 scale and disease incidence was accounted for ULCD. The urdbean genotypes evaluated were grouped into different categories based on disease reaction. The present results indicated that genotype P-104 was immune to YMD, CLS and ULCD, two genotypes, P-102 and P-103 exhibited resistance to YMD and CLS and P-101 showed susceptibility to YMD but immune to CLS. Two genotypes PU 14-11 and P-107 showed highly resistance to both YMD and CLS but susceptible to ULCD. The genotype PU 14-7 showed moderately susceptible to YMD and CLS but immune to ULCD. Rest of the genotypes were moderately to highly susceptible. It is concluded that 3 genotypes (P-104, P-102 and P-108) could be exploited for resistance breeding of urdbean against YMD, CLS and ULCD and P-104, PU 14-7 and PU 14-1 for ULCD. The urdbean genotypes P-105, P-108, P-109 and PU 14-1 could be the choice for resistance against ULCD.